NLP commercialisation in the last 25 years. (May 2019) - Dale, Robert
Abstract: The Journal of Natural Language Engineering is now in its 25th year. The editorial preface to the first issue emphasised that the focus of the journal was to be on the practical application of natural language processing (NLP) technologies: the time was ripe for a serious publication that helped encourage research ideas to find their way into real products. The commercialisation of NLP technologies had already started by that point, but things have advanced tremendously over the last quarter-century. So, to celebrate the journal's anniversary, we look at how commercial NLP products have developed over the last 25 years.